Design and development of self-healing coating based on thiol-epoxy reactions - KAHRAMAN, MEMET VEZİR (ELSEVIER, 2019)
Cracks caused by the effects of mechanical or chemicals forces on coatings may cause their performance to deteriorate and may shorten their lifetime. The microcapsules used for self-healing coatings provide automatic recovery and extend the life of the coatings. In this study, polyurea-formaldehyde epoxy resin (PUF-epoxy) microcapsules were synthesized by in-situ polymerization; because, they allow the size control of the microcapsules, the thickness of the shell can be controlled, its production is easy, it is cheap and combinable with industry. Synthesized microcapsules were characterized by Fourier Transform Infrared Spectroscopy (ATR-FTIR), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM), optical microscope, UV spectrum, zeta analyzer and contact angle measurements. As a result of the thermal analysis, the core (epoxy) content of the microcapsules was 57% by weight and 60% by the extraction method based on the principle of selective dissolution, and these two values were compatible with each other. The average microcapsule diameter was found as 185 nm. For the first time in the literature, an epoxy-containing microcapsule was added to the thiol-containing coating material and a self-healing coating was prepared. The epoxy-containing microcapsules were artificially cracked and the epoxy resin released from it reacted with the thiol received in the coating. For this reason, it was observed that the artificial scratches formed on the coatings showed good self-healing properties.
Keywords: Thiol; Self-healing; Coating; Microcapsule; Epoxy; CURING AGENT; LINSEED OIL; MICROCAPSULES; AMINE; MICROENCAPSULATION; PERFORMANCE; FABRICATION; MERCAPTAN; RESIN